Investing in Water Infrastructure : Capital, Operations and Maintenance - Rodriguez, Diego J. (World Bank, Washington, DC, 2014)
This paper provides background information for development practitioners in the water and other infrastructure sectors. It outlines the major challenges related to financing the gap in global water infrastructure, including those systems that provide urban and rural water supply, and sanitation and irrigation services. Water infrastructure finance includes costs for capital works as well as the operations and maintenance costs that motivate sustainable service delivery. Section one introduces the linkages between water infrastructure and growing global challenges, including food and energy security as well as climate change. Section two describes investment needs in the sector and details various traditional funding sources. Section three proposes a five step reform cycle for making better use of limited funding in the sector. Tools for making these improvements are outlined in section four. The paper concludes with section five, a summary of the challenges and recommendations for the way forward.